China’s ‘CivilOlympic’ Performances and (Re)gained Global Visibility - Puppin, Giovanna (Annali di Ca’ Foscari: Serie Orientale, 2021)
This article investigates how China fantasised about itself and the Beijing 2008 Olympics through the award-winning TV public service announcements (PSAs) of the Beijing Opera Series, with a focus on visibility. By drawing on theories of the spectacle, I perform a semiotic analysis of the most recurrent signs, organising them according to the main themes that emerge. The theatre stage – which represents the Olympic stage – is closely linked to China’s dream of owning the Games and its desire for global visibility. The performance includes the theatrical performance of the Beijing Opera and the performance of civilisation, which semiotically over-determines the Games. The protagonists include famous actors and roles of Beijing Opera (i.e. Dan, who is an anthropomorphic metaphor for China), as well as ordinary people, who are extraordinary for their high degree of civilisation. The spectators, especially through the intradiegetic presence of a Western male Other, validate the country’s performative success and confirm its achieved global visibility.